PAEDERUS ALFIERI EXTRACT INDUCES APOPTOSIS IN HUMAN MYELOID LEUKEMIA K562 CELLS - EL-HAFEEZ, AMER ALI ABD; MOHAMED RAKHA, OSAMA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The rove beetle Paederus alfieri Koch. (Coleoptera: Staphylinidae) is well-known among natural enemies in Egypt as an important predator of agricultural insect pests, it used as an essential agent in the integrated pest management programs. Recent studies have revealed that Paederus may have anti-proliferative effect; however, its mechanisms remain unclear. The aim of the present study is to investigate the anticancer effect of P. alfieri extract (PAE) on K562 human myeloid leukemia cancer cells and elucidation of its mechanism. Methods: Human myeloid leukemia K562 cells were treated with PAE at different concentrations. Cell proliferation was measured using the3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Apoptosis was evaluated using flow cytometry analysis. The expressions of Bcl-2, Bax, active caspase-3, t-Akt, and p-Akt were evaluated by western blotting. Results: PAE has a dose-dependent antiproliferative effect against K562 cells. The half maximal inhibitory concentration was estimated as212±2.3 ng/ml. Flow cytometric analysis showed that PAE induces apoptosis in a dose-dependent manner in K562 cells. We also investigated the molecular mechanism of PAE-induced apoptosis. PAE downregulated Bcl-2 and upregulated Bax and cleaved caspase-3 proteins. Furthermore, the levels of p-Akt are dose-dependently decreased in response to PAE, whereas the total Akt protein levels remained constant during PAE treatment. Conclusion: Taken together PAE-induced apoptosis in human myeloid leukemia K562 cells by modulating PI3K/Akt pathway. Our findings suggest that may be PAE is a good extract for developing anticancer drugs for human myeloid leukemia cancer treatment. Keywords: Paederus alfieri, Pederin, K562, Apoptosis, PI3K/Akt pathway.